Evaluating the Value of uPAR of Serum and Tissue on Patients With Cervical Cancer - Jing, Jiexian (J Clin Lab Anal, 2014)
We investigated the relationship between the urokinase type plasminogen activator receptor (uPAR) in sera and tissues of patients with cervical cancer and the clinical and pathological features of the cancer. Immunohistochemistry (SABC method) was used to detect uPAR expression in cervical cancer and normal tissues; ELISA was employed to assay the uPAR levels in cervical cancer and normal tissues and the corresponding sera. The immunohistochemistry results showed that there were 37 cases of uPAR expression in 56 patients of cervical cancer with a positive expression rate of 66%, whereas there was no uPAR expression in normal cervical tissues. The uPAR levels in cancer tissue from patients with cervical cancer (70.92 ± 28.55 ng/100 mg protein) were significantly higher than those of adjacent tissues obtained from the cancer patients (11.01 ± 5.40 ng/100 mg protein) (P < 0.001). Furthermore, the tissue uPAR levels are correlated with the TNM stages, lymph node metastasis, and the degree of differentiation instead of tumor‐infiltrating and vessel thrombosis. Serum uPAR levels of patients (2.38 ± 0.29 ng/ml) were significantly increased compared with health control group (0.50 ± 0.16 ng/ml) (P < 0.001). Single‐factor analysis shows that the serum uPAR levels of preoperative patients are related with clinical grade, lymph node metastasis, vein embolism, and the depth of infiltration instead of tumor differentiation. We conducted multiple regression analysis and found that the factors affecting preoperative serum suPAR include clinical stage (P = 0.000), pelvic lymph node metastasis (P = 0.000), and depth of myometrial invasion (P = 0.001). The serum suPAR levels of patients with cervical cancer after surgery are significantly decreased compared with preoperation (P < 0.001). The uPAR levels of serum and tissue present a positive correlation (r = 0.705, P < 0.001). The soluble uPAR in serum (suPAR) may be a more convenient indicator to reflect the uPAR system activity in vivo. It could be a tumor marker for clinical diagnosis, treatment, and prognosis monitor of cervical cancer.